2016
DOI: 10.1159/000452515
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Net-Work Meta-Analysis of Upper Gastrointestinal Hemorrhage Interventions

Abstract: Background/Aims: Upper gastrointestinal hemorrhage (UGH) is a serious medical condition which affects a large number of individuals. Endoscopic therapy accompanied by medication is a standard approach that is used to improve the prognosis of UGH patients and a few medications have been developed including proton pump inhibitors (PPIs), histamine H2 receptor antagonist (H2RA), somatostatin analogues and tranexamic acid. This study is set to compare the efficacy and safety of various medical intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
9
0
5
Order By: Relevance
“…• Пациентам с лабораторно и эндоскопически подтвержденным язвенным кровотечением с целью его остановки в рамках других мероприятий по достижению гемостаза рекомендуется внутривенное введение ингибиторов протонного насоса [35,36].…”
Section: уровень убедительности рекомендаций в (уровень достоверностиunclassified
See 1 more Smart Citation
“…• Пациентам с лабораторно и эндоскопически подтвержденным язвенным кровотечением с целью его остановки в рамках других мероприятий по достижению гемостаза рекомендуется внутривенное введение ингибиторов протонного насоса [35,36].…”
Section: уровень убедительности рекомендаций в (уровень достоверностиunclassified
“…Комментарии: Остановке язвенных кровотечений и снижению риска развития повторных кровотечений способствует применение ИПН [35]. При этом одномоментно болюсно внутривенно вводится 80 мг эзомепразола** с последующей непрерывной внутривенной инфузией этого препарата (в дозе 8 мг в час) в течение 72 часов [36].…”
Section: уровень убедительности рекомендаций в (уровень достоверностиunclassified
“…One additional systematic review and network meta‐analysis, published in 2016, compared somatostatin to placebo, proton pump inhibitors, and histamine H2 receptor antagonists in patients with upper gastrointestinal hemorrhage (not limited to variceal bleeding). The authors included 47 randomized trials (n = 9528), reporting no significant all‐cause mortality benefit or the risk of rebleeding, similar to the Cochrane review. Somatostatin was not superior to other pharmacologic agents.…”
Section: Narrativementioning
confidence: 99%
“…The role of tranexamic acid in upper gastrointestinal bleeding has been controversial 3,10 . A meta‐analysis published in 2014 found that tranexamic acid may have a beneficial effect on mortality, but the authors called for additional research on the topic due to some methodological weaknesses of the primary studies 11 .…”
Section: Introductionmentioning
confidence: 99%